Analisis Pengaruh Kebijakan Fiskal dan Inflasi Terhadap Pendapatan Nasional dan Nilai Tukar di Indonesia - Miswar, Miswar; Shaputri, Ela (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2023)
This study aims to analyze the effect of fiscal policy and inflation on national income and exchange rates in Indonesia. This research uses path analysis method (path analysis). Path analysis is a technique to analyze causal relationships that occur in multiple linear regression if the independent variables affect the dependent variable not only directly but also indirectly. Quantitative data analysis was conducted to determine whether the independent variables had an effect on the related variables using the path analysis research method. The results of this study indicate that fiscal policy has a positive and significant effect, inflation has a positive and insignificant effect on national income, fiscal policy and inflation has a positive and significant effect on the exchange rate, national income has a negative and insignificant effect on the exchange rate in Indonesia. The results of the path analysis show that fiscal policy indirectly has a negative effect on the exchange rate with national income as the intervening variable, inflation indirectly has a negative effect on the exchange rate with national income as the intervening variable.